Problems with enuresis management—A personal view - Nevéus, Tryggve (Frontiers in Pediatrics, 2022)
Much has happened since the end of the era when enuresis was blamed on the parents or the children themselves. Still, there are large gaps in our knowledge and large parts of modern enuresis management guidelines are (still) not based on firm evidence. In this review I will question the following commonly made assumptions regarding enuresis evaluation and treatment: • It is important to subdivide enuresis according to the presence of daytime symptoms • Voiding charts are crucial in the primary evaluation of the enuretic child • All children with enuresis need to be screened for behavioral or psychiatric issues • Concomittant daytime incontinence needs to be successfully treated before addressing the enuresis • Concomittant constipation needs to be successfully treated before addressing the enuresis • Urotherapy is a first-line treatment against enuresis This review will show that much of what we do with these children is based more on experience and well-meant but poorly supported assumptions than on evidence. Some advice and therapies are probably ineffective whereas for other treatments we lack reliable predictors of treatment response. More research is obviously needed, but awaiting new results enuresis management could be substantially simplified